2019
DOI: 10.5829/ijee.2019.10.02.02
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Cooling the Photovoltaic Modules by Fins to Improve Power Generation: Economic Assessment

Abstract: Photovoltaic (PV) power plant is one of the most important renewable power generation methods, which is rapidly developing. One of the weak points of PV power plants is the negative effects of increasing the cells temperature on their power generation. In this study, a simple and low cost method is proposed to reduce the temperature of these panels. The use of fins has been proven in many industrial applications and here it is used as coolant of PV panel. This experiment was performed in maximum operating temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This was attributed to the higher value of h for the case of internal cooling than that for the natural and external cooling methods. The reduction in temperature of the Si solar cell achieved in this study has been compared with the results obtained by other cooling methods reported in the 27 Farhanet al, 28 Firoozzadeh et al, 29 Hasan et al, 30 Krstic et al, 31 AI-Amri et al, 32 Ahmad et al, 33 Raina et al, 34 Hernandez-Perez et al, 35 literature and is summarized in Table 2. Apparently, the internal active cooling method proposed in this study offered a relatively higher temperature reduction in comparison to passive cooling and analogous external active cooling methods.…”
Section: ■ Experimental Methodsmentioning
confidence: 67%
“…This was attributed to the higher value of h for the case of internal cooling than that for the natural and external cooling methods. The reduction in temperature of the Si solar cell achieved in this study has been compared with the results obtained by other cooling methods reported in the 27 Farhanet al, 28 Firoozzadeh et al, 29 Hasan et al, 30 Krstic et al, 31 AI-Amri et al, 32 Ahmad et al, 33 Raina et al, 34 Hernandez-Perez et al, 35 literature and is summarized in Table 2. Apparently, the internal active cooling method proposed in this study offered a relatively higher temperature reduction in comparison to passive cooling and analogous external active cooling methods.…”
Section: ■ Experimental Methodsmentioning
confidence: 67%
“…The solar cell is normally surrounded by high-thermal-conductivity radiators. The radiator expands the heat transfer field from the solar cell to the surrounding atmosphere [19,20]. Because of its versatility and low cost, it has remarkable potential to cool PV panels.…”
Section: D) Heat Sink Cooling Stratyegymentioning
confidence: 99%
“…Moreover, the exact location of thermal sensor behind the PV panel is shown in Figure 2. More information about the setup is available in [34,35].…”
Section: Setup Descriptionmentioning
confidence: 99%